2018
DOI: 10.2169/internalmedicine.9743-17
|View full text |Cite
|
Sign up to set email alerts
|

Signet-ring Cell Carcinoma Derived from a Main Duct-type Intraductal Papillary Mucinous Neoplasm of the Pancreas: A Case Report with Long-term Follow-up

Abstract: We herein report the case of a 74-year-old man who underwent surgery 9 years after his initial visit and who was pathologically diagnosed with signet-ring cell carcinoma (SRCC) derived from a main-duct-type intraductal papillary mucinous neoplasm (MD-IPMN). At the first imaging examination, only a small pancreatic cyst with mild dilation of the main pancreatic duct (MPD) was detected in the pancreatic head. Eventually, MD-IPMN with mural nodules and MPD dilation (30 mm) developed in the pancreatic body, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…According to the study using the Surveillance, Epidemiology, and End Results database from 2000 to 2014, the incidence of pancreatic SRCC is 0.4-0.5% among all cases of pancreatic carcinoma [1]. Among the eight cases reported thus far (Table 1) [4][5][6][7][8][9][10][11], surgical treatment with radical resection, pancreatoduodenectomy, and/or total pancreatomy could be performed in four cases, and there was only one case of borderline-resectable tumor treated with neoadjuvant chemotherapy with gemcitabine.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study using the Surveillance, Epidemiology, and End Results database from 2000 to 2014, the incidence of pancreatic SRCC is 0.4-0.5% among all cases of pancreatic carcinoma [1]. Among the eight cases reported thus far (Table 1) [4][5][6][7][8][9][10][11], surgical treatment with radical resection, pancreatoduodenectomy, and/or total pancreatomy could be performed in four cases, and there was only one case of borderline-resectable tumor treated with neoadjuvant chemotherapy with gemcitabine.…”
Section: Discussionmentioning
confidence: 99%
“…From available case reports in the literature, the age at diagnosis of pancreatic SRCC ranged from 61 to 88 years. Mausam Patel et al, in their population‐based study, reported the mean age to be 66.6 years.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports describe findings on CT which range from showing no significant changesto identification of a diffuse tissue mass involving the pancreas . Sakai T. et al reported a case of pancreatic SRCC detected as main pancreatic duct dilation, found primarily in the pancreatic body, with multiple mural nodules identified on CT scan …”
Section: Discussionmentioning
confidence: 99%
“…Currently, 12 case reports have been published in the English literature concerning primary SRCC of the pancreas. [5][6][7][8][9][10][11][12][13][14][15][16] Previously, Patel et al searched 497 pancreatic SRCC patients diagnosed between January 1, 1973, and December 31, 2013, SEER database and focused on determining the predictive effects of epidemiological factors and treatment interventions, with 1-, 2-, and 5-year overall survival (OS) rates of 17%, 9%, and 4%, respectively, which demonstrated very poor survival. [17] And Wu et al [18] identified 24,171 SRCC patients of different tumor locations from the SEER database and 441 pancreatic SRCC accounts for just 1.8%.…”
Section: Introductionmentioning
confidence: 99%